The effect of Internet use on adolescent nutritional outcomes: evidence from China - Weigang Liu; Yanjun Ren; Jian Liu; Jens-Peter Loy (Journal of Health, Population and Nutrition, 2025)
The increasing prevalence of adolescent overweight and obesity poses significant public health challenges, particularly in China. With the rapid adoption of the Internet, adolescents' lifestyles, including dietary habits and physical activity levels, have undergone substantial changes. However, the causal relationship between Internet use and adolescent nutritional outcomes, especially in transitional economies, remains underexplored. This study employs longitudinal data from the China Health and Nutrition Survey (CHNS) and China Family Panel Studies (CFPS) to investigate the impact of Internet use on adolescents' BMI-for-age z-scores and overweight status. An endogenous switching regression (ESR) model addresses potential self-selection bias. Heterogeneity analyses examine urban–rural and gender differences, while mechanism analyses identify dietary pathways influencing outcomes. Internet use increases BMI-for-age z-scores and the likelihood of being overweight among adolescents, with more intensive Internet use further amplifying these effects. These effects hold across urban and rural areas as well as for both boys and girls, though the magnitude may vary. Mechanism analyses suggest that Internet use enhances protein intake while also leading to higher consumption of fast food and soft drinks. Internet use increases BMI-for-age z-scores and overweight risks among adolescents, reinforcing the need for targeted interventions to mitigate its negative health impacts. Policies promoting healthier online behaviors and better access to nutritional education are essential to ensuring that adolescents develop healthy lifestyle habits in the digital age. Addressing these challenges can help policymakers develop equitable health strategies for adolescents in transitional economies.
Keywords: 300; Internet use; nutritional outcomes; BMI-for-age z-score; overweight